A new species of Zwicknia Murányi (Plecoptera, Capniidae) from the French and Swiss Jura Mountains, the French Massif Central, and the French Middle Rhône Region - Reding, Jean-Paul G.; Launay, Bertrand; Ruffoni, Alexandre; Vinçon, Gilles; Boumans, Louis (Zootaxa, 2016)
A new species of Zwicknia Murányi, Z. ledoarei sp. n., from the Jura Mountains of France and Switzerland, the French Massif Central, and the French Middle Rhône Region, is described on the basis of morphology and molecular methods. Information on the distribution and the ecological preferences of this new species is also provided.